A case study analysis : Ingress Corporation Berhad / Anizat Tarlan, Ahmad Rizkhan Abd Wahab Zen and Mohd Hafiz Azmi - Tarlan, Anizat; Abd Wahab Zen, Ahmad Rizkhan; Azmi, Mohd Hafiz (Faculty of Business and Management, 2000)
Ingress established in one of the world's fastest growing region. At Ingress, the development of a culture that strives for excellence in everything that one does is the management preoccupation. Continues improvement in technology and products is achievable through workforces who are spurred by belief that quality in infinite; excellence is the continues processes that has no ending, only the beginning.